Effect Of Lowing Long-Term Levels Of Ionizing Radiation On Some Of Physiological Parameters and Oxidative Stress Among Radiologic Technologists - Marwa Karim Taha; Asaad Taha Al-Douri; Haifa Saeed Lattif (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Technicians in radiology departments are continuously exposed to ionizing radiation, which can affect biological systems. This study aimed to investigate the effects of low-level ionizing radiation (IR) on antioxidant enzymes and blood components in radiology personnel. The study involved forty participants aged 30 to 45 years, divided into three groups: G1 as the control group (n=10), G2 consisting of 15 radiologists, and G3 comprising 15 radiology technology workers. Participants in G2 and G3 had work experience ranging from 5 to 15 years and were employed in X-ray and CT scan departments at General K1 Hospital, Kirkuk. The measured parameters included white blood cells (WBCs), platelets, and lymphocytes, as well as malondialdehyde (MDA), superoxide dismutase (SOD), total antioxidant capacity (TAC), and albumin as indicators of redox status. The results showed a significant increase in MDA levels among radiology workers compared to the control group, while SOD, TAC, and albumin levels decreased (P<0.05). Additionally, radiation-exposed workers had a higher mean count of WBCs and lymphocytes than the control group (P<0.05), whereas platelet levels were significantly lower (P<0.05). This study indicates that occupational radiation exposure can cause short-term changes in blood cells and increase the circulating redox state in healthcare workers operating in CT and IR environments compared to those not exposed to radiation. These findings highlight the importance of regular health monitoring for radiology personnel to mitigate potential long-term effects of radiation exposure.